Ultrastructural identification of basic abnormalities as clues to genetic disorders of the epidermis - Anton-Lamprecht, Ingrun (The journal of investigative dermatology, 1994)
The present article discusses specific, directly gene-dependent ultrastructural markers of dominantly inherited epidermal disorders that serve as clues to their underlying molecular genetic abnormalities. These are epidermolysis bullosa simplex Koebner and Weber-Cockayne with rupture or non-assembly of basal cell keratins and point mutations in keratins 5 and 14. Clumping of basal cell keratins is pathognomonic of EB Dowling-Meara and caused by mutations in hot spots of the rod domain of K 5 and K 14. Clumps and aggregates of basal keratins occur side by side in the same cell and thus do not indicate specific different types of mutations. Similar clumping of suprabasal keratins in bullous CIE Brocq and in palmoplantar keratoderma Voerner have been assigned to identical types of mutations in the same critical position of the rod domain in K 1, K 10, and K 9, respectively. Highly unusual tubular keratins are pathognomonic of another dominant palmoplantar keratoderma type the genetic basis of which still awaits elucidation. Shell formation of (low molecular weight?) keratins in ichthyosis hystrix Curth-Macklin is not linked to the keratin gene clusters on chromosomes 12 and 17 and might be related to regulatory genes of keratin expression. Suprabasal shells in congenital reticular ichthyosiform erythroderma do not consist of keratins but resemble glycoprotein networks. Finally, the keratohyalin abnormality in ichthyosis vulgaris was the clue for the identification of a filaggrin deficiency, at the same time giving evidence to the heterogeneity of keratohyalin proteins.
Elektronische Reproduktion der Druck-Ausgabe 20. Juli 2016
Gesehen am 19.10.2023